2015
DOI: 10.1007/s40534-015-0082-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and modeling of highway truck traffic volume variations during severe winter weather conditions in Canada

Abstract: This paper investigates the impact of cold and snow on daily and hourly truck traffic volume on a primary highway in Alberta, Canada. This research is based on a detailed case study of 5 years of weigh-in-motion data recorded continuously at Leduc site on Highway 2A. Influence of the winter conditions on truck type distribution is examined by classifying trucks into single-unit trucks, single-trailer, and multi-trailer units. It is evident from the study that proportion of the three truck classes in the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In their model (see Equation 3), the independent variable Expected Volume Factor (EVF) contribution was significantly higher as compared to snow and cold while estimating the daily traffic volume. Roh et al [10,11,17] also used similar models (see Equations (1) and (2)) and it was found that the EDVF can explain about 78% of classified traffic variation. These studies along with other similar studies as shown in Table 1 fail to explain the relationship between the traffic variation, snowfall and temperature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In their model (see Equation 3), the independent variable Expected Volume Factor (EVF) contribution was significantly higher as compared to snow and cold while estimating the daily traffic volume. Roh et al [10,11,17] also used similar models (see Equations (1) and (2)) and it was found that the EDVF can explain about 78% of classified traffic variation. These studies along with other similar studies as shown in Table 1 fail to explain the relationship between the traffic variation, snowfall and temperature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An investigation of the impact of snowy days on daily truck traffic volume factor is carried out using data collected from the different type of highway facilities. In Canada, Roh and Sharma [10] studied variations in highway truck traffic triggered by serious winter weather conditions. In their study, the traffic volume factor (y i ) was estimated with Equation (1) by considering snowfall, temperature, and expected daily volume factor (EDVF) as independent variables in the dummy variable regression model.…”
Section: Introductionmentioning
confidence: 99%
“…Weekend volumes are more susceptible to inclement weather conditions since trips are usually more cancellable (Al Hassan and Barker 1999;Datla and Sharma 2008;Cools et al 2010). In a similar manner, truck volume decreases much less than smaller vehicles, likely because truck drivers operate on strict schedules and do not have flexibility to cancel trips for inclement weather (Call 2011;Roh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, their study and other similar studies published in the literature were conducted solely on the basis of total traffic volume data. A few of researches (Roh et al 2012(Roh et al , 2015(Roh et al , 2016a(Roh et al , 2016b concluded that total traffic and passenger car volumes are influenced by both the snowfall and the cold temperatures, but the truck volume is not significantly affected by the amount of snowfall or severity of cold tem-peratures. Described in these papers are an extension of the research that was reported by Roh et al (2012).…”
Section: Introductionmentioning
confidence: 99%